Vehicle modelling and washout filter tuning for the Chalmers Vehicle Simulator - Murgovski, Nikolce (My University, 2007)
The Chalmers Vehicle Simulator (CVS) was built by students in 1999 and is constantly being upgraded ever since. The main objective is to provide a realistic simulation environment for students to perform projects and master thesis works, investigating and testing new products and ideas relevant to the car industry. It consists of a hexapod motion platform (Stewart platform) and five computers responsible for the simulation. A quarter of a Volvo car (the part where the driver sits) is mounted on the platform and the visual cues are projected on a screen in front of the driver. The algorithm that transforms the desired vehicle motion into realizable simulator motion commands is called a washout filter. The washout filter is responsible for keeping the motion platform within its physical boundaries and for stimulating the driver to feel that driving the simulator is close to driving a real car. The washout filter “washes out” cues below the driver’s perception threshold and returns the platform state to the neutral position. It calculates the platform position and angular displacement in real time, taking the desired translational acceleration and angular displacement as an input signal. Washout filters have been widely investigated, mainly in the field of flight simulations. In this work three washout filters originally developed for NASA airplane simulators are considered for the CVS. The Classical and Optimal washout filters are implemented for real-time use, while the Adaptive washout filter is tested only by off-line simulation. The quality of a washout filter depends on how realistic motion it produces. This goal is achieved by minimizing the difference between the measured sensed accelerations and rotations that a driver feels in a real car, with those the driver feels in the simulator. The sensed accelerations and rotations are determined by a mathematical model of the human vestibular system which is mainly responsible for motion sensations. An interesting feature of the vestibular system is that it does not differentiate between accelerations produced by translational movement and accelerations produced by tilting the driver’s head with respect to the gravity vector. This phenomenon is known as “tilt coordination” and makes it possible to simulate low frequency translational accelerations by tilting the platform. This augments the high frequency acceleration cues produced by the washout filters. The washout filter parameters are tuned by optimization algorithms. A Genetic Algorithm is used to find a starting point in the parameter space for the ensuing local optimization where a Riccati Algebraic Solver and the Steepest Descent Method are used. The optimization is performed on a computer simulation model of the CVS, taking standard driving maneuvers as inputs. The obtained Classical and Optimal washout filters were tested in real time on the CVS with several “test drivers”. During all the tests, the platform never hit the physical boundaries, but moved very close to them, thus using most of the actuator’s movement. According to the test drivers’ suggestions some of the input signals were rescaled. After the final adjustments their impression was that the washout filters produced realistic driving experience.
Keywords: Transport; Optimeringslära, systemteori; Reglerteknik; Signalbehandling; Teknisk fysik; Transport; Optimization, systems theory; Control Engineering; Signal Processing; Engineering physics